2005
DOI: 10.2139/ssrn.846304
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Evaluation of Structural Credit Risk Models

Abstract: This paper evaluates the capacity of five structural creditrisk models to forecast default rates. In contrast to previous studies with similar objectives, the paper employs firm-level data and finds that model-based forecasts of default rates tend to be unbiased and to deliver point-in-time errors that are small in both statistical and economic terms. In addition, inand out-of-sample regression analysis reveals that the models account for a significant portion of the variability of credit risk over time but fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 22 publications
0
17
0
2
Order By: Relevance
“…the coexistence of unusually rapid expansion in credit and asset prices, have useful predictive content for subsequent widespread financial distress, output weakness and disinflation, over horizons of two to four years ahead, depending on the calibration Lowe, 2002, 2004). Moreover, such macro indicators can also help to improve the predictive content of popular micro models of default risk, including those widely used in the financial industry (Tarashev, 2005).…”
Section: From Local To Global Effectsmentioning
confidence: 99%
“…the coexistence of unusually rapid expansion in credit and asset prices, have useful predictive content for subsequent widespread financial distress, output weakness and disinflation, over horizons of two to four years ahead, depending on the calibration Lowe, 2002, 2004). Moreover, such macro indicators can also help to improve the predictive content of popular micro models of default risk, including those widely used in the financial industry (Tarashev, 2005).…”
Section: From Local To Global Effectsmentioning
confidence: 99%
“…Los trabajos que evalúan empíricamente los distintos métodos son escasos y en general no abordan el problema con un enfoque estructural. Algunos ejemplos son Tarashev (2005), Switzer and Wang (2013), Altman et al (2010), Bharath and Shumway (2008) y Kato and Hagendorff (2010). En este sentido, en este documento se adapta el modelo estructural de Goldstein et al (2001) a los datos de balance y mercado de las firmas del sector financiero que cotizan en el mercado de valores de Colombia.…”
Section: Revisión De Literaturaunclassified
“…Dado que no se tiene una estimación de este valor en Colombia, se escogió siguiendo la aproximación propuesta enTarashev (2005).…”
unclassified
“…Similarly, Zhu (2008) observed that replacing the Gaussian distribution of asset return with three alternative non-Gaussian distributions signifi cantly improves their performance. Tarashev (2008) found that with fi rm-level data, both the exogenous and endogenous structural credit risk models tend to account for the level of default rates observed in the market.…”
Section: Literature Reviewmentioning
confidence: 99%